ASSESSMENT OF PROBLEMS AFFECTING THE STRUCTURE, CONDUCT AND PERFORMANCE OF COWPEA MARKETING IN YOLA NORTH AND YOLA SOUTH LOCAL GOVERNMENT AREAS IN ADAMAWA STATE, NIGERIA. - GIREI, A.A.; DIRE, B.; SALIHU and M. M. ILIYA, M. (British Journal of Marketing Studies, 2013)
The study assesses the socio-economic and problems affecting the structure, conduct and performance of cowpea marketing in Yola South and Yola North Local Government Area of Adamawa State, Nigeria. The data used for the study was mainly from primary source. These were obtained through the administration of structured questionnaire to a sample of 75 cowpea marketers in the two local government areas. The data generated was from marketers in 2011/2012 marketing season. Descriptive statistics were employed for the study to examine the socio-economic characteristics of marketers and the constraint faced in their marketing activities. The study concludes that, several problems were associated with cowpea marketing in the study area namely; inadequate capital, pest infestation, and low profit, high cost of transportation, bad road network, storage, high taxes, inadequate market information and lack of standard measure are some of the problem militating against cowpea marketing in the study area. Amongst all the problems inadequate capital, pest infestation and low profit ranks the first three most serious problems. The study therefore recommends that, Government and the private sector should facilitate the marketers in accessing a timely and affordable credit facility so as to sustain and expand their marketing activities. Government should open up and rehabilitate the road network in the hinterland to facilitate easy evacuation of agricultural inputs and commodities in and out of the market.